Optical Nerve Sheath Diameter (ONSD) Ultrasonography as Intracranial Non-Invasive Pressure Measurement in PostOperative Patient EDH Evacuation in ICU - Saputro, Ramadhan; Adipurna, Resa Putra; Laksono, Buyung Hartiyo (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2025)
Intracranial Pressure (ICP) monitoring is an important component in the management of severe Traumatic Brain Injury (TBI) in ICU. Periodic ICP monitoring in patients with severe TBI who were treated in ICU resulted in lower mortality rates than those who were not measured. ICP can be measured by invasive or non-invasive methods. Invasive measurements related to higher cost, while non-invasive tests such as MRI and CT scans are associated with radiation exposure. ONSD ultrasound is an alternative examination that is practical, inexpensive, without radiation, and can be performed bedside. We report a case in the ICU of RSUD Dr. Saiful Anwar Malang, male, 44 years old, had a traffic accident, and was diagnosed with severe TBI with GCS E2V2M4, right frontotemporal 36cc epidural hematoma, cerebral edema, and left posterolateral 4th rib fracture. The patient underwent epidural hematoma surgical evacuation. Postoperatively, the patient was treated in ICU. We performed periodic ONSD ultrasound and with the guidance of these examinations the patient's management could be adjusted. Within 48-hours postoperatively the patient could be extubated and then moved to ward. ONSD ultrasound could be done bedside so that clinicians could quickly and precisely adjusted the management according to the dynamic condition of the patient.